DEVELOPMENT OF LANGUAGE (Analisis Urgensi bagi peserta didik Perspektif Psikologi Dan Islam) - Achmad Baihaqi; M Mansyur (LP2M IAI Miftahul Ulum Pamekasan, 2019)
This discussion aims to provide insights in developing language based on psychological and Islamic perspectives. In psychological perspective, the ability to develop children's language at ages 4-11 years (learners at the Play Group level until Elementary School grade 5), they must increase their vocabulary continuously increase, language style changes change, and it is better with fluent communication. Developing language in an Islamic perspective is very important, because basically humans have the potential that was needed from birth. In developing language for students, it is necessary to increase the potential in Him to emerge belief, faith, and piety for God. In the learning process pay attention to how to choose the teacher, access the learning environment and honesty of the teacher in the delivery of material so that in developing the language of students able to make students hope that their God, looking for things that haqq and inner, find out religion and general by getting used to yourself to God Almighty, then find good norms and be able to socialize with the community well so that students can become human beings (perfect humans) in their lives.